Spatio-Temporal Parameters\' Changes in Gait of Male Elderly Subjects - Heydar Sadeghi; Hamid Reza Norouzi (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The purpose of this study was to compare spatio-temporal gait parameters between elderly and young male subjects. Methods & Materials: 57 able-bodied elderly (72±5.5 years) and 57 healthy young (25±8.5 years) subjects participated in this study. A four segment model consist of trunk, hip, shank, and foot with 10 reflective markers were used to define lower limbs. Kinematic data collected using four high speed video based cameras at a sampling frequency of 90 Hz.The t-testfor independent samples (α≤0.05) applied for statistical analysis. Results: Significant differences showed longer stance phase (2%), longer push-of time (4%), slower cadence (13%), slower speed (28%) and shorter step length (15%) for elderly in comparison with young subjects, though no significant differences were seen in double supporttime between two groups. Conclusion: Due to results, spatio-temporal changes are mainly attributed to the age-related decreases in muscular flexibility, joints>ranges of motion and neuromuscular control in elderly people.